Echocardiographic Normal Reference Ranges for Non-invasive Myocardial Work Parameters in Pediatric Age: Results From an International Multi-Center Study - Sabatino, Jolanda; Leo, Isabella; Strangio, Antonio; Bella, Sabrina La; Borrelli, Nunzia; Avesani, Martina; Josen, Manjit; Paredes, Josefa; Piccinelli, Enrico; Sirico, Domenico; Pergola, Valeria; Fraisse, Alain; et al. (Frontiers in Cardiovascular Medicine, 2022)
Aims. This international multi-center study aimed to demonstrate feasibility and reliability of non-invasive myocardial work (MW) parameters in paediatric population, providing normal reference ranges for this useful echocardiographic tool in this specific subset of patients. Methods and results. One hundred fifty healthy children and adolescents (mean age of 10.6±4.5, 91 males) have been enrolled in this in this retrospective multi-center study involving three Paediatric laboratories. A complete echocardiographic examination has been performed, including Global longitudinal strain assessment. The following parameters of Non-invasive MW have been obtained through a dedicated software: Global work index (GWI), global constructive work (GCW), global work waste (GWW), and global work efficiency (GWE), using LV strain loops and non-invasive brachial artery cuff pressure values. The lowest expected values were for GWI 1723 mmHg% in males and 1682 mmHg% in females, for GCW 2089 mmHg% and 2106 mmHg%, for GWE 95.9% and 95.5% whereas the highest expected value for GWW was 78 mmHg% in men and 90 mmHg% in women. The univariable and multivariable analysis showed significant associations between either GWI or GCW with SBP (β coefficient=0.446, p<0.001; β coefficient=0.456, p<0.001 respectively) and LV GLS (β coefficient=−0.268, p=0.001; β coefficient=−0.233, p=0.003 respectively). Inter- and intra-observer variability showed good reproducibility of non-invasive MW parameters. Conclusion. Non-invasive MW parameters were feasible and reliable in paediatric population. This study provided normal reference ranges of these useful echocardiographic indices.